Direct Photoexcitation of Borate Enabling Minisci Reaction. Issue 1 (5th November 2021) - Kemmochi, Marin; Miyamoto, Yusuke; Sumida, Yuto; Ohmiya, Hirohisa
Abstract: The photoexcitable borate enabling Minisci C−H alkylation of heteroarene has been described. This protocol using alkylborate only needed O2 and visible light, which provides a considerably clean system. The direct photoexcitation of alkylborate allowed the generation of tertiary, secondary, and primary ‐alkyl radical including methyl radical. This light‐driven Minisci reaction gave a choice for the functionalization of heteroarenes. Abstract : The photoexcitable borate enabling Minisci alkylation of heteroarene has been described. This protocol using alkylborate only needed O2 and visible light, which provides a considerably clean system. The direct photoexcitation of alkylborate allowed the generation of tertiary, secondary, and primary ‐alkyl radical including methyl radical.